Chronic hand eczema: A prospective analysis of the Swiss CARPE registry focusing on factors associated with clinical and quality of life improvement - Cazzaniga, Simone; Diepgen, Thomas L. (Contact dermatitis, 2018)
Background Hand eczema (HE) is common and may follow a chronic disease course. So far, prospective studies investigating the risk factors for disease progression as a prerequisite for targeted prevention are scarce. Objective To evaluate the overall association of HE-associated factors with clinical and quality of life (QoL) improvement during a follow-up of 2 years. Methods Data of the prospective patient cohort (N = 199) followed by the Swiss chronic HE (CHE) registry on long-term patient management (CARPE-CH) were analysed by means of both classic regression and semantic map analyses. Results Both severity of HE and QoL significantly improved over the period of 2 years (P < .001). However, 20% of patients had moderate to severe HE after 2 years of follow-up. As factors associated with an unfavourable CHE clinical course and QoL, environmental exposures, male sex, occupational skin disease, job loss or change at baseline, allergic contact dermatitis, a chronic disease course, palmar localization and widespread eczema were identified. Conclusions Analysis of prospective data from CARPE-CH shows a complex pattern of associations among variables as shown by semantic map and classic statistical analyses. Factors related to occupational exposure had the highest impact on CHE.